The Influence of a Work Environment that Supports Employee Health and Wellness and Human Resource Development on Employee Performance at PT Pusri Palembang - Fauzi, Yusuf (Politeknik Siber Cerdika Internasional, 2025)
This research aims to analyze the effect of a work environment that supports employee health and wellness and human resource development on employee performance at PT Pusri Palembang. The research objectives are to assess the extent to which these factors influence employee performance and to provide actionable recommendations for improving workplace practices and employee development strategies. The research employs a quantitative research method with a multiple linear regression analysis approach to determine the relationship and significance of the variables. The population comprises all 1,692 permanent employees of PT Pusri Palembang. Using the proportional sampling method, a sample of 100 employees from various compartments led by Super Vice Presidents (SVPs) was selected. The findings reveal that both a supportive work environment and human resource development have a positive and significant impact on employee performance. The research suggests that leaders should recognize and reward employees delivering excellent results and provide appropriate training and resources, particularly for employees assigned roles misaligned with their education and skills.